KAJIAN ETNOMEDISIN DAN PEMANFAATAN TANAMAN OBAT PADA DESA TERPILIH KECAMATAN SECANG KABUPATEN MAGELANG - Alfian Syarifuddin; Nufikha Falyauma; Imron Wahyu Hidayat (Jurnal Farmasi Klinik dan Sains, 2022)
Traditional medicine is a mixture of various types of plant parts in an area, so that local wisdom related to traditional medicine needs to be studied, preserved, and developed. This requires supporting data, namely in the form of written documentation and documented images with the aim of knowing various types of medicinal plants, types of diseases, how to mix, and how to treat them. This type of research is a descriptive qualitative research with snowball sampling technique. The inclusion criteria in this study, among others: the residents of the Secang District who have sufficient knowledge and experience in traditional medicine, are willing to be informants in the study, people who are over 30 years old. The results showed that the community in 5 villages, Secang District, Magelang Regency used 107 species of medicinal plants from 54 families. The plant parts used are leaves, stems, roots, flowers, seeds, rhizomes, fruits, tubers, all plants, bark, wood, and fruit skins. The results of the above calculations obtained sample results for 5 villages, which amounted to 387 respondents with a 95% confidence level. ICF analysis is used to determine the level of homogeneity between the information provided by the respondents. In this study, there were a total of 80 types of disease, based on the results of the ICF calculation, the value that was close to 1 was 45 efficacy, while the ICF value that was close to 0 was 35 efficacy